CLINICAL SURVEY ON EQUINE LAMENSS IN THE PROVINCE OF MOSUL, MOSUL, - T. Abass, B.; J. Eesa, M.; J. Amin , A. (The Iraqi Journal of Veterinary Medicine, 1996)
During the 100 yaers (358) horses were examined for detection of lameness. The result of detailed investigation reveiled that (91) and (45) horses with fore and hind limb lameness respectively. Lameness were found to be originated from the fore limb were included shoulder, elbow, radius, carpal, metacarpal, fetlock, phalanx and hoof regions at (0.7%), (5.1%), (2.9%), (12.5%), (15.6%), (9.6), (7.3%) and (13.9%) respectively. While the hind limb lameness were included in thigh, stiffle, tibial. tarsal, metatarsal, fetlock, phalanx and hoof regions at (0.7%), (2.9%), (0.7%), (8%), (8.8%), (1.4%), and (3.3%), respectively.